The south, slavery, and the black folk`s soul-crushing in "My Father`s Name" by Lawrence P. Jackson - Ettien, Yapo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of this paper is to examine the particular oppressive experiences of Blacks who became the beast of burden of the peculiar institution, a system of dehumanization that reduced them to simple objects in the South. In "My Father?s Name", through the study of a black Virginia family and its neighborhood, Lawrence P. Jackson makes a recall of the horror of slavery and Blacks` struggle for freedom in the Postbellum South.
Keywords: soul-crushing; slavery; otherness; dehumanization; alienation